Konsekuensi Putusan Mahkamah Konstitusi Nomor: 46/PUU-VIII/2010 Terhadap Hak Mewaris Anak Luar Kawin Dalam Perspektif Hukum Nasional - Achmad Khozin Baharudin; Septian Arya Budi Mahesa; Fadila Fernanda (Jurnal Indonesia Sosial Sains, 2023)
The legality of an illegitimate child in Indonesia has been fundamentally regulated in the Indonesian Civil Code in Article 280 and the admission is stated in Article 284, if the child has been avowed by the biological father upon the biological mother’s approval. The problem arise in the Constitutional Court Adjudication Number: 46/PUU-VIII/2010 about the Inheritence Right of an Inllegitimate Child, which became a normic problem that makes as if there is a dualism in the familial system; inside and outside legal marriage, in which this is considered as legalizing non-marriage relationship among Indonesian citizens. Another problem arise about the distribution of inheritance law for illegitimate children in the Constutional Court Adjudication Number: 46/PUU-VIII/2010 about the Inheritence Right of an Inllegitimate Child, that makes an illegitimate child have the same inheritance right with a legitimate child. Surely, this does not align with the Principle of Justice, especially for the legitimate child. The research method used in this Journal is the normative law research, which is a textual law research that leans into normic law that exists in the international regulations and legislational regulations, this research especially uses the Constitutional Court Number: 46/PUU-VIII/2010 about the Inheritence Right of an Inllegitimate Child, and the Indonesian Civil Code.